Brand equity in Caribbean financial services: the moderating role of service providers. Issue 3 (20th December 2019) - Rambocas, Meena; Arjoon, Surendra
Abstract : Purpose: The purpose of this paper is to develop an integrated model to represent how service experience (core, employee and service scale), customer satisfaction (transaction-specific and cumulative) and brand affinity influence brand equity in financial services, taking into account the moderating influence of financial service providers. Design/methodology/approach: Data were collected from 751 customers in three types of financial service providers (banks, insurance companies and credit unions), and analyzed with structural equation modeling and multi-group analysis. Findings: The findings confirm the significant and positive influence of service experience, customer satisfaction and brand affinity on brand equity. Employee service experience has the strongest influence, but its impact is mediated by customer satisfaction. Brand affinity has the lowest influence on brand equity. The type of financial service provider moderates the influence of customer satisfaction on brand equity; transactional satisfaction is more important for credit unions and insurance companies, but cumulative satisfaction is higher for banks. Practical implications: The study is significant for three reasons. First, it reconciles branding strategies across different types of financial service providers. Second, it will help financial managers to develop and implement a more integrated approach toward building brand equity for financial service brands. Finally, it will identify specific service-related areas financial providers can target to increase customers' preferential value. Originality/value: The paper addresses previous concerns within brand equity studies by examining the drivers of brand equity formation in multiple financial institutions. It shows how different aspects of service experience and customer satisfaction affect brand affinity and preferential attitudes toward financial brands.